(untitled) (Research, Society and Development, 2021)
This paper reports, describes and discusses the data on the prevalence of leprosy in Bahia, also making a comparison with other Brazilian regions about this infection, since it deals with the occurrence in all age groups, and Brazil is one of the countries that contains more cases of leprosy in the world, predominating in people over 60 years old, totaling 24.7% of all cases (World Health Organization, 2017). From the data provided by the DATASUS platform on the frequency of leprosy diagnosis in Bahia in men and women from the period 2017 to 2021 it is observed a higher total frequency in men among the years analyzed, being that the total number of cases in women was 4947 cases and in men was a total of 6154 diagnoses, thus representing 1207 more cases in men compared to women. Evaluating chart 1, which deals with the frequency of leprosy cases in all age groups, it is observed the highest occurrence of cases among children and adolescents from 10 to 15 years old, in the entire period of the data collected, corresponding to a total of 52.32% of all infections reported in Bahia, according to data from DATASUS. Moving on to young people and adults aged 20 to 59 years, those infected corresponded with a total of 33.36%, being the second group that contained the most infected in the Bahia region, and finally, the elderly aged 60 to 80 years or more, representing 14.32% of leprosy patients, being the group that suffered the least infections in all the years analyzed since 2017. From the analysis of graph 2, it is observed the data regarding the total number of leprosy cases in Bahia and the Northeast, diagnosed in the period from 2017 to 2021, and in the first year analyzed, the diagnoses in Bahia totaled 24.09% of the total in the northeastern region, being the highest percentage of the analyzed periods, and, the lowest percentage was in 2021, totaling 11.82% of the cases in the Northeast. The socioeconomic profile of cases in the state of Bahia, considered an endemic area and the largest state in the Northeast, is similar to the profile of the total number of cases throughout Brazil. The detection coefficient in 2017 was classified as high (14.5 cases per 100,000 inhabitants), and 79.4% of cases were cured.